2014
DOI: 10.1109/jlt.2014.2345580
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Static Disorder on Sensitivity of Coupled Resonator Optical Waveguide Gyroscopes

Abstract: Coupled resonator optical waveguides (CROWs) have shown theoretical promise as microoptical integrated gyroscopes with sensitivities exceeding comparably sized MEMS gyroscopes. Here, we analyze the effect of static disorder on the rotational sensitivity of a CROW gyroscope. Since CROWs consist of a onedimensional array of evanescently coupled ring-shaped microresonators, disorder includes random variations of the resonator optical path length and couplings between them resulting from manufacturing errors. We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…According to 22 44 45 46 , the resolution (which is defined as the minimum detectable angular rate) is expressed if the resonator is circular:…”
Section: Resultsmentioning
confidence: 99%
“…According to 22 44 45 46 , the resolution (which is defined as the minimum detectable angular rate) is expressed if the resonator is circular:…”
Section: Resultsmentioning
confidence: 99%
“…changes in the quality factor (or roundtrip loss) of resonators and fluctuations in the coupling coefficient between resonators. According to reference [19], the performance of gyro is relatively stable with respect to fluctuations in the coupling coefficient. So, we only discuss the influence of the variations of perimeter and quality factor.…”
Section: Numerical Analysis and Discussionmentioning
confidence: 99%
“…We introduce the fluctuations into our model by randomly changing the quality factor of each single ring and the radius of them. The Gaussian probability distributions [19] have been used to model the random fluctuations. When we model the fluctuations of quality factor, the radiuses of the resonators are fixed, the mean value of the Gaussian probability distribution is chose to be = Q 10 mean 7 and the standard deviations δ Q are Q 0.1 mean , Q 0.2 mean and Q 0.3 mean , respectively.…”
Section: Numerical Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another multipath resonant structure for gyroscope applications is based on a coupled spiral interferometer that is a spiral waveguide with coupling between adjacent arms [14], having a maximum sensitivity decreasing as the reciprocal of the waveguide loss coefficient. Finally the disorder effects affecting the performance of CROW gyroscopes and largely associated with the fabrication tolerances are discussed in [15,16]. Some potential applications have been identified for the 1D photonic crystal (i.e., Bragg grating) assisted ring resonator, called in this paper the Bragg grating ring resonator (BGRR), such as for add-drop filters and angular velocity sensors [17][18][19][20], but any specific study under rotation conditions has been not yet reported.…”
Section: Introductionmentioning
confidence: 99%